Evaluasi Pengalaman Pengguna pada Aplikasi Mobile Learning dengan menggunakan UX Honeycomb - Wirahadi Kusuma; Retno Indah Rokhmawati; Mahardeka Tri Ananta (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Ruangguru is a technology-based company focused on education services that has more than 10 million users and manages more than 150 thousand teachers throughout Indonesia. Ruangguru has become the largest mobile learning application in Indonesia and can be well received by its users. But according to the results of a conducted survei, 86.5% of them had experienced problems when using the Ruangguru application. These problems are related to the ux honeycomb aspect. This study uses a quantitative data approach obtained from an online questionnaire distributed to Ruangguru users with the criteria of users aged 13-18 years. Then each aspect of the ux honeycomb is analyzed by the entropy weighting method. Entropy is weighted by several stages. Stages carried out include normalizing data, calculating the number of normalized data values, calculating entropy values, and calculating entropy weights. The results of this study are sequences of aspects that affect user experience. The order of aspects of the highest value is usable, findable, useful, accessible, credible, and desirable. Based on this sequence, respondents considered that the desirable aspect was the aspect with the lowest value. The low aspect is because Ruangguru has not been able to bind emotional closeness with its users.This lack of emotional closeness occurs because community functions that can interact with each other in Ruangguru have not yet been built. To improve it, discussion services can be made between users while watching learning videos.